Assessment of hydrogen production from waste heat using hybrid systems of Rankine cycle with proton exchange membrane/solid oxide electrolyzer. (5th March 2023) - Nasser, Mohamed; Hassan, Hamdy
Abstract: A techno-economic assessment of hydrogen production from waste heat using a proton exchange membrane (PEM) electrolyzer and solid oxide electrolyzer cell (SOEC) integrated separately with the Rankine cycle via two different hybrid systems is investigated. The two systems run via three available cement waste heats of temperatures 360 °C, 432 °C, and 780 °C with the same energy input. The waste heat is used to run the Rankine cycle for the power production required for the PEM electrolyzer system, while in the case of SOEC, a portion of waste heat energy is used to supply the electrolyzer with the necessary steam. Firstly, the best parameters; Rankine working fluid for the two systems and inlet water flow rate and bleeding ratio for the SOEC system are selected. Then, the performance of the two systems (Rankine efficiency, total system efficiency, hydrogen production rate, and economic and CO2 reduction) is investigated and compared. The results reveal that the two systems' performance is higher in the case of steam Rankine than organic, while a bleeding ratio of 1% is the best condition for the SOEC system. Rankine output power, total system efficiency, and hydrogen production rate rose with increasing waste heat temperature having the same energy. SOEC system produces higher hydrogen production and efficiency than the PEM system for all input waste heat conditions. SOEC can produce 36.9 kg/h of hydrogen with a total system efficiency of 23.8% at 780 °C compared with 27.4 kg/h and 14.45%, respectively, for the PEM system. The minimum hydrogen production cost of SOEC and PEM systems is 0.88 /kg and 1.55 /kg, respectively. The introduced systems reduce CO2 emissions annually by about 3077 tons. Highlights: Hydrogen production from waste heat via PEM and SOEC hybrid systems is studied. Raising the waste heat temperature for the same energy input increases the system's performance. Maximum hydrogen production of SOEC and PEM is 36.9 kg/h and 27.4 kg/h, respectively. The minimum hydrogen production cost of the SOEC system is 0.88 /kg, and that of PEM is 1.55 /kg. The introduced systems reduce CO2 emissions annually by about 3077 tons.